PW-laser produced MeV proton beams stopped in WDM plasmas (H, He, Ar, N, Xe) - Deutsch, Claude; Chen, Sophia; Fuchs, Julien (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
Physical processes involved in the interaction of ion beams in Warm Dense Matter (WDM) (i.e. 1-100 eV. 0.01-100 g/cc) is fundamental to the understanding of condensed matter, solidstate physics, fusion sciences, and astrophysical phenomena...
Keywords: proton beams; plasma; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics